LQTS Parents' Reflections About Genetic Risk Knowledge and their Need to Know or Not to Know their Children's Carrier Status. Issue 6 (1st May 2014) - Mangset, Margrete; Hofmann, Bjørn
Abstract: Long QT syndrome (LQTS) is a contributor to unexplained deaths in infants (SIDS), children, teenagers and young adults. A gene test result may allow for individual tailored treatment, but also pose a burden of knowing one's carrier status, with no treatment recommendation. Genetic risk knowledge in the case of LQTS can promote adjustment and coping, but also fear anxiety, ambivalence and moral dilemmas. This makes it challenging to respect both the right to know and the right not to know. The purpose of this study was to explore LQTS parents' perception of genetic knowledge, and their need to know or not to know about their children's carrier status. Qualitative, semi structured interviews were conducted with thirteen parents of LQTS‐children. Results show that parents found it important to know the result of a gene test for LQTS including their children's carrier status. The risk was framed and incorporated into their everyday life and their life perspectives. Pertinent moral dilemmas concerned information disclosure to children and relatives. Parents thought that early and gradual disclosure to children would promote coping. Parents' moral dilemmas were rarely addressed during encounters with healthcare providers. The participants had several suggestions for improvement in that regard.